Spontaneous Subgaleal Hemorrhage in a Child with Autism - Jennifer W. Glusman; Kathryn Doherty; Anne K. Doran (Journal of Pediatric Health And Nutrition, 2023)
Severe ascorbic acid (Vitamin C) deficiency, commonly known as “scurvy,” continues to be a problem in malnourished populations across the world but is relatively rare in the United States. Early features of this condition include general weakness, fatigue, and aching limbs. An extremely rare and late feature of this condition is subgaleal hemorrhage. Scurvy has such a low prevalence in First World countries that it is often misdiagnosed or not diagnosed at all. The subject in this case report presented acutely and is one of few to involve a subgaleal hemorrhage to be documented in medical literature to date. Laboratory studies and clinical improvement through treatment established the diagnosis. Ascorbic acid deficiency should be considered when evaluating children with poor nutrition despite socioeconomic status, living conditions, or access to health care. This case also reminds us that neurodivergent children are a vulnerable population and more research will need to be conducted to determine just how detrimental the pandemic has been to patients with ongoing problems who were lost to follow up.
Keywords: Pediatrics